Exploring Lived Experiences of Married Pakistani Women Post-Mastectomy - Laila Hussain; Zeenatkhanu Kanji; Sharifa Lalani; Shabnam Moledina; Abida K Sattar (Elsevier, 2019)
Objective: This qualitative descriptive exploratory study aimed to explore the lived experiences of married Pakistani women, 2 years post-mastectomy. Methods: Twelve participants were recruited through purposive sampling from outpatient oncology clinic from a tertiary care hospital in Pakistan. Interviews were audio-taped and transcribed, and then themes and sub-themes were identified. Results: Women verbalized a range of their experiences throughout the span from diagnosis to mastectomy. One over arching theme, quality of life and four main themes and their subthemes emerged from the data. Following are the themes; from history to diagnosis, worries, coping strategies, and recommendations. Conclusions: The study findings revealed that effective coping strategies were beneficial for these women, as these women coped well after being diagnosed with breast cancer. Strong recommendations were made by the participants for the formulation of support groups, which could help them reduce their anxiety through information exchange.